Life strategy of Astyanax lacustris (Characiformes: Characidae) in different habitats of the Upper Paraná River basin - Fernandes, Augusto Gabriel Jatobá; Oliveira, Gabriela Correia de; Santos, Lucas Henrique dos; Luiz, Matheus Chueire; Andrade, Luccas Machado de; Pena, Gabriele Rossatto; Orsi, Mario Luis (Acta Scientiarum. Biological Sciences, 2025)
The current study was carried out in the Tibagi River basin, an important tributary of the Paranapanema River, in the southern region of Brazil. Research with fish from the Neotropical region is extremely important to understand the ecological dynamics of the region. In this context, we chose to study the reproductive variables of the species Astyanax lacustris, a Characiform known in the region for its reproductive plasticity and great importance in the trophic chain. The study area contained four data collection points, namely Limoeiro, Três Bocas, Congonhas I, and Congonhas II, where individuals of A. lacustris were collected using different capture methodologies. In total, 1553 individuals were collected, with 100% consistency in all stretches. Congonhas I and Congonhas II provided 76.3% of the total number sampled. In general, it was noted that the females of the species are more represented in the longer length classes, while males are more abundant in the shorter length classes, except for the Congonhas II stretch, where females were more abundant in all length classes. Analysis of oocytes collected from 639 females indicates that the species A. lacustris spawns in installments, and that its reproduction is conditioned and modified by biotic and abiotic environmental issues.